Altered ageing behaviour of a nanostructured Mg-8.2Gd-3.8Y-1.0Zn-0.4Zr alloy processed by high pressure torsion. (1st June 2018) - Sun, W.T.; Qiao, X.G.; Zheng, M.Y.; Xu, C.; Kamado, S.; Zhao, X.J.; Chen, H.W.; Gao, N.; Starink, M.J.
Abstract: In this study, the ageing behaviour of a nanostructured Mg-8.2Gd-3.8Y-1.0Zn-0.4Zr (wt.%) alloy produced by solution treatment followed by high pressure torsion (HPT) was systematically investigated using hardness testing, high resolution high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM), elemental mapping, X-ray diffraction (XRD) and XRD line broadening analysis. The HPT-deformed alloy exhibits an ageing response that produces a higher peak-aged hardness at lower temperature and shorter ageing time as compared to the same alloy aged after conventional thermomechanical processing. The HAADF-STEM and elemental mapping reveal extensive segregation of solute atoms along grain boundaries during ageing. A model is developed which shows that the main structures causing hardening for peak-aged samples are the grain boundaries and the segregation of solute atoms formed along grain boundaries. The metastable β′ phase precipitates, which form on ageing of conventionally processed Mg-Gd-Y-Zn-Zr alloy samples, do not form in the present aged samples, and instead equilibrium β-Mg5 (RE, Zn) phase forms on over-ageing. This altered precipitation behaviour is attributed to the high defect density (e.g. grain boundaries, dislocations and vacancies) introduced by HPT, leading to enhanced diffusion of solutes. The present processing produces an alloy that has a hardness of ∼145 HV. A model of strengthening indicates that whilst grain boundary strengthening provides the largest contribution to strengthening, it is the additional solid solution hardening, cluster hardening, and dislocation hardening that provide the main factors that caused the hardness to surpass that of other bulk processed Mg alloys studied to date. Graphical abstract: Image 1